Sharing lights on the way to God Muslim-Christian dialogue and theology in the context of Abrahamic partnership - Valkenberg, Pim 1954- (Currents of encounter : studies on the contact between Christianity and other religions, beliefs, and cultures, 2006)
This book seeks to give form to a theology that hyphenates two traditions that have not only been in constant conflict during most of their historical encounters but are also presented as opposite blocks in the threatening 'clash of civilizations' at the beginning of the third millennium: Islam and Christianity. Based on experiences of dialogue between the three Abrahamic faiths, this book analyzes historical and contemporary processes of interreligious dialogue between Christians and Muslims in order to arrive at a concept of dialogue as 'mutual emulation.' It shows how, in their theologies